Edukasi Bahan Tambahan Pangan Bagi Siswa Siswi SMP N. 5 Nekamese Kabupaten Kupang - Winioliski Winioliski; Aldiana Aldiana; Agnes Agnes; Marni Marni (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
In an effort to bolster food safety awareness, the Community Service Team from the Department of Medical Laboratory Technology at Poltekkes Kemenkes Kupang launched an initiative. Its goal was to educate students about the dangers associated with Food Additives, or Bahan Tambahan Pangan (BTP), per the Indonesian Ministry of Health Regulation No. 33 of 2012. BTP encompasses substances not typically found in everyday food and may or may not provide nutritional value, intentionally added to various food products. The initiative's primary focus was on two hazardous additives: borax and formalin. Students were taught simple, effective methods for detecting these substances using natural ingredients like turmeric and papaya latex. This community outreach occurred in the village of Bone, Nekamese Regency, East Nusa Tenggara, and featured lectures, interactive sessions, and hands-on demonstrations. The results were promising, as participants gained a deeper understanding of the hazards associated with these additives and acquired skills to identify them. This initiative empowers a safer, more informed generation of consumers, championing food safety.